2022
DOI: 10.21608/mid.2022.133445.1302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and serotypes of Streptococcus pneumoniae among under five children attending Toro general hospital, Bauchi State, Nigeria

Abstract: Background:Streptococcus pneumoniae(S. pneumoniae)is an important pathogen responsible for numerous infections in humans particularly children under 5 years causing unparalleled fatality.Aim:This study set out to determine the prevalence and circulating serotypes of Streptococcus pneumoniaein under 5 years old children attending Toro General Hospital, Bauchi State, Nigeria.Methods:The study was cross-sectional, and hospital based. A total of 114 nasopharyngeal swabs were collected from children < 5 years old.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The 50% decline in pneumonia admissions over the 9-year period was borderline significant, suggesting a smaller effect of the PCV on pneumonia admissions than on mortality or case-fatality 28 . While PCV reduces the severity and incidence of pneumonia among the strains it targets 29 , previous studies have shown that the introduction of PCV can lead to an increase in the proportion of pneumococcal pneumonia due to nonvaccine pneumococcal serotypes 30,31 . It is possible that in Uganda, like other African countries, other serotypes are taking the place of those targeted by PCV.…”
Section: Discussionmentioning
confidence: 99%
“…The 50% decline in pneumonia admissions over the 9-year period was borderline significant, suggesting a smaller effect of the PCV on pneumonia admissions than on mortality or case-fatality 28 . While PCV reduces the severity and incidence of pneumonia among the strains it targets 29 , previous studies have shown that the introduction of PCV can lead to an increase in the proportion of pneumococcal pneumonia due to nonvaccine pneumococcal serotypes 30,31 . It is possible that in Uganda, like other African countries, other serotypes are taking the place of those targeted by PCV.…”
Section: Discussionmentioning
confidence: 99%